ERICO CURADO E A TRADIÇÃO LITERÁRIA BRASILEIRA - Freitas e Souza, Enivalda Nunes (Organon, 2012)
This article aims to discuss Brazilian Literature trajectories, focusingspecifically on the poet Eurico Curado’s works. Curado, whose poetic oeuvres reachmodernism, introduced symbolism in Goiás State. His 1928’s essay upon the modernmovement, and his poem “Carnaval do sertão” (“Backland Carnival”) – which findsformal and theme-related aspects in the modern literary techniques – are analyzedso as to evince how the author deals with the Brazilian Literary tradition.